La irrupción borgoñona en la escultura castellana de mediados del siglo XII - Senra Gabriel y Galán, Jose Luis (Anuario del Departamento de Historia y Teoría del Arte, 1992)
During the central decades of the twelfth century, the influence of the emblematic abbey at Cluny is perceived in some monasteries from Castilla-Leon. This institutional influence, when the monarchy relaxes its support to the French House, is coincident with the conclusion of the work in the large burgudian masonries. Two traditional Castilian monasteries. San Salvador de Oña and San Pedro de Cardeña, are the direct receivers of those workshops’ expansion. From that moment onwards, the codification of a series of resources and technical solutions seem to take place which, slowly watering down, will be present in most of the sculpture from the second half of the twelfth century.